Building common ground: how facilitators bridge between diverging groups in multi-stakeholder dialogue - Grimm, Julia (Journal of business ethics, 2024)
The effectiveness of multi-stakeholder initiatives (MSIs) in tackling grand social and environmental challenges depends on productive dialogue among diverse parties. Facilitating such dialogue in turn entails building common ground in form of joint knowledge, beliefs, and suppositions. To explore how such common ground can be built, we study the role of different facilitators and their strategies for bridging the perspectives of competing stakeholder groups in two contrasting MSIs. The German Partnership for Sustainable Textiles was launched in an initially hostile communicative environment, whereas the Fossil Free Sweden Initiative proceeded in a fertile communicative environment. We trace how the facilitators in these initiatives achieved common ground through three bridging strategies—communicative integration, temporal calibration, and process alignment—adapted to the communicative environments of these MSIs. In hostile communicative environments, facilitators achieve common ground by steering diverging stakeholder groups towards ‘reconciling’ their different language registers, knowledge bases, and meaning systems to ‘meet in the middle’ on points of agreement and shared interests. In fertile communicative environments characterised by greater mutual trust, facilitators can steer interactants to ‘strategically appropriate’ to the language, knowledge, and meaning system of a particular stakeholder group to win this group’s support. Our analysis contributes to a better understanding of how productive multi-stakeholder dialogue can be facilitated.